2000
DOI: 10.1038/sj.leu.2401706
|View full text |Cite
|
Sign up to set email alerts
|

A real-time PCR assay for the quantification of residual malignant cells in B cell chronic lymphatic leukemia

Abstract: Several new therapeutic approaches for the treatment of monoclonal B cell lymphomas are currently being investigated. In parallel with new therapeutic modalities, more sensitive diagnostic methods are needed. These methods should be highly sensitive in detecting very low amounts of malignant cells and should be specific for the malignant clone. In addition, these methods should allow the quantification of residual tumor cells. In this study a new real-time polymerase chain reaction (LightCycler) was evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1
2

Year Published

2001
2001
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 25 publications
(25 reference statements)
0
24
1
2
Order By: Relevance
“…Thus, our data demonstrate higher sensitivity of ASO IgH RQ-PCR compared to our MRD flow assay in post-transplant CLL patients. This contradicts in vitro data that had predicted sensitivities of ASO IgH RQ-PCR [21][22][23] within the same order of magnitude as for MRD flow approaches (one CLL cell in 10 4 -10 5 normal cells). 18,25,29,30 We therefore analyzed factors that influence specificity and sensitivity of MRD flow as the apparently less sensitive method.…”
Section: Figurecontrasting
confidence: 56%
See 2 more Smart Citations
“…Thus, our data demonstrate higher sensitivity of ASO IgH RQ-PCR compared to our MRD flow assay in post-transplant CLL patients. This contradicts in vitro data that had predicted sensitivities of ASO IgH RQ-PCR [21][22][23] within the same order of magnitude as for MRD flow approaches (one CLL cell in 10 4 -10 5 normal cells). 18,25,29,30 We therefore analyzed factors that influence specificity and sensitivity of MRD flow as the apparently less sensitive method.…”
Section: Figurecontrasting
confidence: 56%
“…It has been reported that MRD determinations by RQ-PCR at a level of 1E-4 resulted in a coefficient of variation (CV) of 32%. 21 For MRD flow (like for all rare cell measurements by flow cytometry 48 ), the CV is dependent on the absolute number of CLL cells acquired. Although we did not formally determine the retest reliability of our assay, at the absolute specificity threshold (20 CLL cells), a CV of about 23% is expected.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, as recently shown, real-time PCR assays may be helpful in analyzing the MRD kinetics. 47,48 In summary, the present report suggests that in CLL patients the probability of obtaining sustained MRD(−) CR after autotransplantation is low and that MRD analysis is useful to predict clinical relapse. On the other hand, the long-lasting responses observed after allogeneic transplants indicate the possibility of a true eradication of CLL in a significant proportion of patients, although delayed responses or transient relapses at MRD level may be detected in some instances.…”
mentioning
confidence: 65%
“…17,20 In the last 4 years, RQ-PCR has become an attractive and useful approach for the detection of MRD in immature B-cell malignancies and the subset of B-CLL without somatic mutations, 17 mainly because of the utilization of consensus probes in the JH region thereby avoiding the need to synthesize allele-specific probes (ASO probes) for each patient, which is very expensive and time-consuming. 18,31 Unfortunately, this approach is less optimal for MRD analysis of postgerminal center derived-B-cell malignancies containing a high level of SH, because of mismatches between the probes/ primers and the mutated VDJH rearrangement. Ladetto et al 14 has suggested that zero or one point mutation in the probe binding site does not influence the effectiveness of the RQ-PCR, and the presence of three or more point mutations in that site is always associated with failure of the RQ-PCR.…”
Section: Discussionmentioning
confidence: 99%